Budget Estimation Planning Web Based Information System Of Project Network Ftth : Sistem Informasi Perencanaan Anggaran Biaya Konstruksi Jaringan Ftth - Mahendra Wijaya; Sumarno (Universitas Muhammadiyah Sidoarjo, 2021)
The planning process in project work is very important to maintain the quality of results and management of work time. In this study, the authors make a web-based information system application and based on work experience while working at PT.Telkom Akses as administrative staff who handles projects or work related to the construction of the FTTH network by PT.Telkom Indonesia. This information system aims to simplify the work in project planning, especially in making BoQ more accurate and more efficient. The method used by the author is the Lyfe Cycle software development method that uses the waterfall model. Using the laravel 7 framework and php 7 this information system was built and mysql 5 as a server, it is hoped that this information system can be useful and facilitate the work of administrative staff at PT. Telkom Akses